Saponin Pada Bawang Putih Lokal Indonesia dan Potensi Biologinya (Saponins in Indonesian Local Garlic and Their Biological Potential) - Balqis; Betty Lukiati; Mohammad Amin; Agus Muji Santoso; Jeni; Widodo (Jurnal Jamu Indonesia, 2022)
This study aims to determine the various kinds of compounds from the saponin group found in local Indonesian garlic and map the biological potential of these compounds, especially the potential in the health sector. Saponins are a group of compounds characterized by the presence of foam. Saponins have various benefits both in the health, agriculture, animal husbandry, and also in the food and cosmetic industries. Fifteen compounds from the saponin group were identified from local Indonesian garlic obtained from West Papua, using Liquid Chromatography Mass Spectrometry (LCMS) and validated based on their similarity with the NCBI PubChem database. Saponin compounds in local Papuan garlic, then, their biological potential was mapped using the PASS Server and showed that there were seventeen kinds of biological potential in the saponin compound group from Indonesian local garlic. The three most dominant potencies are as anticancer, antifungal, and hypolipemic. Based on this research, it can be concluded that Indonesian local garlic has great potential to be developed and applied in the health sector, especially as an anticancer related to the saponin content in tubers.